Comparison of the evolution and creation theories - Dawley, Frank Andrew (My University, 1895)
Introduction: Someone has said, “If the Evolutionists theory of the origin of the universe is true the Creation theory must surely fall.” This is a statement that is generally believed by those that have not thoroughly investigated both theories, and it is even believed by some of our brightest minds.
Citation: Dawley, Frank Andrew. Comparison of the evolution and creation theories. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Evolutionist theory; Creation theory; Comparison; Theses; Manuscripts (documents)